Komparasi Kawasan Heritage Braga dan Mall Paskal 23 di Bandung - Gaby Christalia Geraldine; Chelsea Angelica Ang; Michelle Elizabeth Sumartono; Raisyha Srikandini (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
Braga is a historic area in Bandung characterized by colonial-era buildings and a distinctive old-town atmosphere that holds significant value in the city’s architectural development. Since the Dutch colonial period, this area has functioned as a social, economic, and cultural center. Paskal 23 Mall a modern urban area with enclosed buildings serving as shopping and entertainment facilities. Comparing these two areas is important to understand spatial changes caused by modernization. Descriptive qualitative method was employed through observation and short interviews. The results indicate that Braga is appreciated for its historical, while Paskal 23 Mall is more organized, cleaner, and comfortable.